Review of the transmission of sound from air to water - JONES, H. W.; KWAN, H. W. (Archives of Acoustics, 1988)
This paper reviews the physical principles relating to the transmission of sound from air to water. The major emphasis is on the effect of the air-water interface on the transmission of sound to an underwater receiver. A limited consideration only is given to non-flat surfaces and the transmission at grazing angles of incidence.